Mechanical circulatory support for cardiogenic shock in takotsubo syndrome - Cammann, Victoria L.; Schweiger, Victor; Szawan, Konrad A.; Di Vece, Davide; Niederseer, David; Würdinger, Michael; Schönberger, Alexander; Schönberger, Maximilian; Koleva, Iva; Mercier, Julien C.; Citro, Rodolfo; Vecchione, Carmine; et al. (Springer Nature, 2026)
Background
Cardiogenic shock complicates takotsubo syndrome (TTS) in approximately 10% of cases. The effectiveness of mechanical circulatory support (MCS) for managing cardiogenic shock in TTS remains unknown.
Methods
We assessed outcomes in TTS patients with cardiogenic shock who received MCS compared to medical therapy only by using data from the International Takotsubo Registry. Two independent propensity scores were computed to investigate outcomes of patients with an intra-aortic balloon pump (IABP) vs. medical therapy only (1:2 propensity score matched cohort) and patients with an Impella vs. medical therapy only (1:1 propensity score matched cohort). The primary endpoint was in-hospital mortality and the secondary outcomes included MCS-related complications.
Results
Among 3740 eligible patients, 309 (8.3%) patients had cardiogenic shock, of whom 112 (36.2%) had MCS and 197 (63.8%) had medical therapy only. After propensity-score matching, the use of an IABP was found to be associated with a lower in-hospital mortality rate than medical therapy only (14.5% vs. 35.5%, P = 0.002), while mortality rates in the Impella group and medical therapy only group were comparable (25.0% vs. 29.2%, P = 0.75). MCS-related complications occurred in 6.0% of the IABP cohort and in 31.3% of Impella cohort.
Conclusion
Active MCS has been increasingly used for the management of cardiogenic shock in patients with TTS. This observational study could not demonstrate an association with improved mortality with an Impella device, but possibly with an IABP when compared to patients with medical management only. MCS-related complications occurred more frequently in the Impella cohort than in the IABP cohort. Further data are required to confirm results of the present study.